Losing without Fighting - Simple Aversive Stimulation Induces Submissiveness Typical for Social Defeat via the Action of Nitric Oxide, but Only When Preceded by an Aggression Priming Stimulus - Rillich, Jan; Stevenson, Paul A. (Frontiers in Behavioral Neuroscience, 2017)
Losing a fight (social defeat) induces submissiveness and behavioral depression in many animals, but the mechanisms are unclear. Here we investigate how the social defeat syndrome can be established as a result of experiencing aversive stimuli and the roles of neuromodulators in the process. While biogenic amines and nitric oxide (NO) are associated with reduced aggression in mammals and insects, their specific actions during conflict are unknown. Although the social defeat syndrome normally results from complex interactions, we could induce it in male crickets simply by applying aversive stimuli (AS) in an aggressive context. Aggressive crickets became immediately submissive and behaved like losers after experiencing two brief AS (light wind puffs to the cerci), but only when preceded by a priming stimulus (PS, stroking the antenna with another male antenna). Notably, submissiveness was not induced when the PS preceded the AS by more than 1 min, or when the PS followed the AS, or using a female antenna as the preceding stimulus. These findings suggest that any potentially detrimental stimulus can acquire the attribute of an aversive agonistic signal when experienced in an aggressive context. Crickets, it seems, need only to evaluate their net sensory impact rather than the qualities of a variety of complex agonistic signals. Selective drug treatments revealed that NO, but not serotonin, dopamine or octopamine, is necessary to establish the submissive status following pairing of the priming and aversive stimuli. Moreover, treatment with an NO donor also induced the social defeat syndrome, but only when combined with the PS. This confirms our hypothesis that aversive agonistic experiences accumulated by crickets during fighting invoke social defeat via the action of NO and illustrates that a relatively simple mechanism underlies the seemingly complex social decision to flee. The simple stimulus regime for inducing social defeat opens new avenues for investigating the cellular control of subordinate behavior and post-conflict depression.